Visualization of radiocesium distribution in surface layer of seafloor around Fukushima Daiichi Nuclear Power Plant - Yukihisa Sanada (Nature Portfolio, 2021)
Abstract Large quantities of volatile radionuclides were released into the atmosphere and the hydrosphere following the Fukushima Daiichi Nuclear Power Plant (FDNPP) accident on March, 2011. Monitoring of radiocesium in sediment is important for evaluating the behavior of radiocesium in the environment and its effect on aquatic organisms. In this study, the radiocesium distribution in the surface sediment around the FDNPP was visualized as a radiocesium concentration map using periodical survey data from a towed gamma-ray detection system. The uncertainty of the radiocesium map was evaluated via comparison with a large amount of sediment core sample data. The characteristics of the radiocesium distribution were examined considering the seafloor topography and a geological map, which were obtained via acoustic wave survey. The characteristics of the formation of 137Cs anomaly at the estuaries were analyzed using a contour map of 137Cs concentration combined with water depth. Validation of the created map showed that it was comparable with actual sediment core samples. The map generated using the towed radiation survey depicted the 137Cs concentration distribution as the position resolution of a 1 km mesh. Finally, the 137Cs concentration decreased with time in consideration of such uncertainty.